Application of Hazard Analysis of Critical Control Point (HACCP) on "Urutan" Chicken Products at Dapur Ayuna Catering - Semariyani, A.A.Made; I Wayan Sudiarta; Ni Made Ayu Suardani Singapurwa (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
This Applied Research is expected to be able to identify, analyze and control the hazards that may occur in the food manufacturing process. Hazard Analysis Critical Control Point (HACCP) is a food safety system by analyzing materials, processes, and food products. HACCP analysis can be used as an effort to control the quality of the final product in order to meet the requirements for healthy, safe, and halal food products. Dapur Ayuna Catering is a catering company for the general public that processes traditional Balinese menus, one of which is a sequence of orders made not only made from pork but also made from chicken meat to meet the wishes of consumers who should not or are allergic to pork and casings. The sleeve used is a synthetic casing made from collagen. This company has implemented HACCP in every food production including in the manufacture of chicken orders. This type of research is descriptive with the method of observation of the production process of chicken (Balinese sausage) menus. The application of HACCP in the production process of Urutan menus is to control the temperature and time during the production process to prevent microbial growth in food. Of the ten applications of HACCP according to Indonesian National Standard SNI No. 01-4852-1998 regarding the HACCP system, only one point of application is not in accordance with SNI, namely monitoring. Monitoring activities are not carried out routinely during the empon-empon washing process in the manufacture of 'basa genep' (Bali complete spices) and the storage of the final product has not been carried out in a special freezer because it is still using a refrigerator for households so that it is still one with other product storage. The HACCP system at the Dapur Ayuna Catering for Urutan chicken products for the general public has been implemented properly starting from receiving raw materials, processing, packaging, labeling, and storage (storage freezer). Critical of every CCP that has been set by Dapur Catering Ayuna Buduk Mengwi Badung. It takes handling and prevention of contamination in every stage of the chicken menu processing process with the aim that the food consumed by consumers is safe from contamination.